Cerebral Microbleeds and Acute Hematoma Characteristics in the ATACH-2 and MISTIE III Trials. (8th March 2022) - Magid-Bernstein, Jessica R.; Li, Yunke; Cho, Sung-Min; Piran, Pirouz J.; Roh, David J.; Gupta, Ajay; Shoamanesh, Ashkan; Merkler, Alexander; Zhang, Cenai; Avadhani, Radhika; Montano, Nataly; Iadecola, Constantino; et al.
Abstract : Background and Objectives: To study the relationship between the presence of cerebral microbleeds (CMBs) and acute hematoma characteristics among patients with primary intracerebral hemorrhage (ICH). Methods: We pooled individual patient data from the Antihypertensive Treatment of Acute Cerebral Hemorrhage 2 (ATACH-2) trial and the Minimally Invasive Surgery Plus Alteplase for Intracerebral Hemorrhage Evacuation phase 3 (MISTIE III) trial. We included individuals with a brain MRI scan. Exposure was the presence of a CMB. The coprimary outcomes were admission ICH volume and hematoma expansion. Mixed-effects linear and logistic regression models were used, with demographics and comorbid conditions considered fixed effects and the study cohort treated as a random effect. Additional analyses assessed the relationship between CMB topography and number and hematoma characteristics. Results: Of the 1, 499 patients with ICH enrolled in the parent trials, 466 (31.1%) were included in this analysis, and 231 (49.6%) patients had CMBs. In adjusted models, presence of CMBs was associated with smaller ICH volume (β = −0.26, 95% confidence interval [CI] −0.44 to −0.08) and lower odds of hematoma expansion (odds ratio 0.65, 95% CI 0.40–0.95; p = 0.04). The strength of association between CMBs and hematoma characteristics increased with increasing number of CMBs. The location of the CMBs and the severity of leukoaraiosis did not modify these results. Discussion: In a pooled cohort of patients with ICH, our results are consistent with the hypothesis that more severe underlying small vessel disease, as represented by CMBs, leads to smaller baseline hematoma volumes and reduced hematoma expansion. Underlying cerebral small vessel disease may be of prognostic significance after ICH. Trial Registration Information: ClinicalTrials.gov Identifier: NCT01176565 and NCT01827046. Classification of Evidence: This study provides Class II evidence that the presence of microbleeds on MRI is associated with a smaller ICH volume at presentation and a lower rate of hematoma expansion on follow-up imaging.